Galician language at the crossroads of multilingualism - Vicente Rodríguez, Denis (Madrygal. Revista de Estudios Gallegos, 2014)
In this paper we conducted a discourse analysis of multilingualism in Europe and Galicia providing a proposal for its renewal with the aim of promoting Galician language.
Keywords: multilingualism; speech; promotion of Galician; Galicia.